The Use of Language in Solving Inverse Algebraic Functions Problems - Méndez-Balbuena, Ignacio; Hermosillo-Abundis, Ana Cristina; Ruge, Diane; Trenado, Carlos; Lemuz-López, Rafael; López-Cortés, Vicente Arturo; Bonilla-Sánchez, María del Rosario; Pelayo-González, Héctor Juan; García-Flores, Marco Antonio (Frontiers in Education, 2022)
Objective: The aim of the present work was to investigate the use of verbal language applied to the solution of inverse function problems in comparison to the algebraic method in students of humanities. Methods: We consider only algebraic functions in our study. Three precalculus problems were chosen and two solution methods used. A total of 120 students participated in this study where 60 of them used the verbal method and the rest the algebraic method. Results: In order to determine if there was a relationship between the utilized method and the effectiveness of the solution, that is the number of exercises solved correctly related to the type of method used, we used Pearson's chi-square test. We found a significant association between the type of method and the success of the solution χ2 (1) = 10.84, p <.001. Regarding the effect size, we found that the probability to get a correct solution was 2.53 times higher when solved with the verbal method in comparison to the algebraic method. Discussion: We suggest that such efficacy in solving inverse function problems was due to the self-regulation of participant’s language. In this sense, it is necessary to investigate the effects of such self-regulation by means of our experimental paradigm in a future study. Conclusions: The results of the present study showed that verbal language applied to the solution of inverse function problems is highly effective as compared to the algebraic method.